SCCmec Genotypes of Methicillin-Resistant Staphylococcus aureus in Nasal Carriage of Multiple Sclerosis Patients in Iran - JAMSHIDI, Yasaman (Iran J Public Health, 2019)
BACKGROUND: Asymptomatic nasal colonization of Methicillin-Resistant Staphylococcus aureus is common in Multiple Sclerosis patients. SCCmec types I to III are mainly attributed to HA-MRSA strains whereas SCCmec types IV and V have commonly been reported in CA-MRSA infections. Here, we assessed the frequency of nasal carriage of MRSA in MS patients. This study aimed to evaluate MRSA SCCmec typing in MS nasal carriage. METHODS: A cross-sectional descriptive study was conducted from Feb and Jun 2017 in MS Research Center, Tehran University of Medical Sciences (TUMS), Iran. Overall, 620 nasal swabs were collected (325 from MS patients and 295 from control group). Antimicrobial susceptibility test was performed using the disk diffusion and E-test method. Presence of mecA gene was confirmed by PCR assay and multiplex PCR was performed for SCCmec typing of MRSA isolates. RESULTS: The frequency of MRSA among the MS patients and control group was almost equal (9.2% and 10.1%, respectively). SCCmec typing detected only types III, IV and V in both groups and type IV was the most predominant type in MS patients and control group. SCCmec type III was more prevalent in control group than MS patients (40% vs. 20%). Moreover, the frequency of SCCmec type V in MS patients was significantly higher than control group (36.7% vs. 3.3%). CONCLUSION: Although most MRSA isolates were collected from inpatients, interestingly there is a high frequency of SCCmec types IV and V in MS group. Moreover, MRSA isolates were not resistant to more antibiotics in SCCmec type III than types IV–V.